2015
DOI: 10.1111/adb.12227
|View full text |Cite
|
Sign up to set email alerts
|

Reflection impulsivity in binge drinking: behavioural and volumetric correlates

Abstract: The degree to which an individual accumulates evidence prior to making a decision, also known as reflection impulsivity, can be affected in psychiatric disorders. Here, we study decisional impulsivity in binge drinkers, a group at elevated risk for developing alcohol use disorders, comparing two tasks assessing reflection impulsivity and a delay discounting task, hypothesizing impairments in both subtypes of impulsivity. We also assess volumetric correlates of reflection impulsivity focusing on regions previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 55 publications
(77 reference statements)
4
60
0
1
Order By: Relevance
“…In line with a previous study in the non-PD population [33] there was no correlation between the beads task and temporal discounting and no difference between the PD group and controls. While in standard temporal discounting tasks rewards are delayed by weeks, in the beads task, drawing more of the beads delays a possible reward only by a few seconds and correct responses resulted in small fixed rewards, compared to anticipated large rewards in temporal discounting tasks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with a previous study in the non-PD population [33] there was no correlation between the beads task and temporal discounting and no difference between the PD group and controls. While in standard temporal discounting tasks rewards are delayed by weeks, in the beads task, drawing more of the beads delays a possible reward only by a few seconds and correct responses resulted in small fixed rewards, compared to anticipated large rewards in temporal discounting tasks.…”
Section: Discussionsupporting
confidence: 91%
“…For example, previous studies on substance abusers showed this cohort gather significantly less evidence on the beads task but did not perform worse on feedback learning and risk taking tasks [42]. Furthermore, a recent study has suggested that the beads task may be particularly sensitive to assess impulsivity as it is visually less explicit and requires individuals to rely on their internal task representation [33], which is not the case in classical risk taking [43] and feedback learning tests.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, increased cognitive impulsivity on the cognitive subscales of the BIS-11 is a well-replicated finding in substance and behavioral addictions, such as gambling disorder and internet addiction (Choi et al., 2014; Marazziti et al., 2014; Zhou, Zhou, & Zhu, 2016). Moreover, previous studies showed similar results of increased reflection impulsivity using the same (Beads) task in a range of addiction-related disorders, such as substance use disorders, gambling disorder, binge drinking, and Parkinson’s disease with medication-induced behavioral addictions (Banca et al., 2016; Djamshidian et al., 2012, 2013). …”
supporting
confidence: 55%
“…More broadly, the capacity to build an internal model of the task structure or environment can potentially be extended to other forms of behavioural inflexibility such as set shifting or reversal learning and forms of impulsivity such as reflection impulsivity (76). Together, these findings highlight a role for (6)).…”
Section: Resultsmentioning
confidence: 99%